Incidence of and Case Fatality Following Acute Myocardial Infarction in Aboriginal and Non-Aboriginal Western Australians (2000-2004): A Linked Data Study - Katzenellenbogen, Judith; Sanfilippo, F.; Hobbs, M.; Briffa, T.; Ridout, S.; Knuiman, M.; Dimer, L.; Taylor, Kate; Thompson, Sandra (Elsevier, 2010)
Background. Despite Coronary Heart Disease exacting a heavy toll among Aboriginal Australians, accurate estimates of its epidemiology are limited. This study compared the incidence of acute myocardial infarction (AMI) and 28-day case fatality (CF) among Aboriginal and non-Aboriginal Western Australians aged 25–74 years from 2000–2004. Methods. Incident (AMI hospital admission-free for 15 years) AMI events and 28-day CF were estimated using person-based linked hospital and mortality data. Age-standardised incidence rates and case fatality percentages were calculated by Aboriginality and sex.Results. Of 740 Aboriginal and 6933 non-Aboriginal incident events, 208 and 2352 died within 28 days, respectively. The Aboriginal age-specific incidence rates were 27 (males) and 35 (females) times higher than non-Aboriginal rates in the 25–29 year age group, decreasing to 2–3 at 70–74 years. The male:female age-standardised incidence rate ratio was 2.2 in Aboriginal people 25–54 years compared with 4.5 in non-Aboriginal people. Aboriginal age-standardised CF percentages were 1.4 (males) and 1.1 (females) times higher at age 25–54 years and 1.5 times higher at age 55–74 years. Conclusion. These data suggest higher CF and, more importantly, AMI incidence contribute to the excess ischaemic heart disease mortality in Aboriginal Western Australians. The poorer cardiovascular health in Aboriginal women, particularly in younger age groups, should be investigated.